Homologous recombination in lung cancer, germline and somatic mutations, clinical and phenotype characterization. (November 2019) - Kadouri, Luna; Rottenberg, Yakir; Zick, Aviad; Hamburger, Tamar; Lipson, Doron; Peretz, Tamar; Nechushtan, Hovav
Highlights: Biomarkers for homologous recombination deficiency suggest high response rate to cisplatinum. High response rate and overall survival were observed in BRCA1/2 carrier lung cancer patients. Exceptional survival of over 5 years in a BRCA1 carrier correlated with high LOH/HRD score in the tumor. Treatment with platinum or PARPi in addition to immunotherapy should be considered in these patients. Abstract: Objectives: Identifying new predictive biomarkers in lung cancer that will prolong survival for additional subgroups of patients is of utmost importance. We report response to treatment and survival among homologous recombination deficient (HRD) lung cancer patients mostly BRCA mutation carriers to better define the predictive value of HRD status among non-small cell lung cancer (NSCLC). Methods: We retrospectively evaluated our genetic and pathology database and identified 14 carriers of germline mutation in BRCA1 (n = 5), BRCA2 (n = 8), or PALB2 (n = 1) and a patient with a somatic BRCA2 mutation. Platinum compounds were part of the initial or follow-on treatment protocols in 9/11 with metastatic disease. Overall survival (OS) and response to platinum were analyzed in these patients. Results: Median OS for the 11 patients was 30 months. The 2- and 3-year survival rates in our cohort were 62.5% and 28.6%, respectively, and 7/10 patients with metastatic lung cancer survived for more than 1 year which compares favorably with the literature. Of eight patients who were treated with platinum compounds, seven responded; however, in two the response endured for <6 months. The Foundation Medicine LOH/HRD genomic score was calculated in three patients and the level was high in 2/3 (66%), including 1/2 tumors in germline BRCA mutation carriers and tumor in the patient with a somatic BRCA2 mutation. In both complete response to platinum was recorded. Conclusion: Response rate to platinum compounds and survival in these patients do suggest that platinum-based therapies should still be incorporated in our treatment regimen for the patients with HRD lung cancer, and that BRCA and other HRR associated gene testing may be important in lung cancer patients.